Answer: f(g(-1)) = -16
Step-by-step explanation:
First, we need to find g(−1), which means we substitute -1 in place of x in the function g(x):
g(-1) = 3(-1) = -3
Next, we substitute g(-1) into f(x):
f(g(-1)) = f(-3) = 3(-3) - 7 = -16
Therefore, f(g(-1)) = -16.
a.4/9
b. 2 4/9
c. 2 1/36
Step 2: 7x – 3x – 4 = 20
Step 3: 4x – 4 = 20Which of these is most likely the next step? (4 points)
4x = 24
4x = 16
4x = 5
4x = 80
-1 ...................................................................you're welcome.